Case Discussion Responsabilidad Social Interna en J-V Resguardo - Jáuregui Keti (2012)
J&V Resguardo is a different security company oriented towards services in general but with personalized attention. Its workforce was highly motivated and skilled. The company managed to distinguish itself from the rest of its competitors thanks to the leadership with the social responsibility of its founders the brothers Pablo and Javier Calvo-Pérez. Practices to improve the quality of life in workers are divided into five dimensions: respect pride impartiality camaraderie and credibility. Each dimension includes a series of programs aimed at improving their development as a person.